2019
DOI: 10.1016/j.isci.2019.01.023
|View full text |Cite
|
Sign up to set email alerts
|

A Non-canonical Pathway with Potential for Safer Modulation of Transforming Growth Factor-β1 in Steroid-Resistant Airway Diseases

Abstract: SummaryImpaired therapeutic responses to anti-inflammatory glucocorticoids (GC) in chronic respiratory diseases are partly attributable to interleukins and transforming growth factor β1 (TGF-β1). However, previous efforts to prevent induction of GC insensitivity by targeting established canonical and non-canonical TGF-β1 pathways have been unsuccessful. Here we elucidate a TGF-β1 signaling pathway modulating GC activity that involves LIM domain kinase 2-mediated phosphorylation of cofilin1. Severe, steroid-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…TGF-β can also stimulate and increase reactive oxygen species (ROS) production that leads oxidant and antioxidant imbalance which in turn can activate latent TGF-β developing a profibrogenic cycle [ 17 ]. Moreover, TGF- β1 is associated with corticosteroids insensitivity in chronic inflammatory diseases including asthma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β can also stimulate and increase reactive oxygen species (ROS) production that leads oxidant and antioxidant imbalance which in turn can activate latent TGF-β developing a profibrogenic cycle [ 17 ]. Moreover, TGF- β1 is associated with corticosteroids insensitivity in chronic inflammatory diseases including asthma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms driving Cofilin1 activation may be different and dependent on RhoGTPase, at least in part. Cofilin1 is specifically phosphorylated by activated LIM domain kinase (LIMK) at the Ser3 residue in response to different stimuli, including TGF-β [39], gamma-secretase [40]. As an actin-binding protein, Cofilin1 regulates actin dynamics through its phosphorylation by the Rac1/PAK1/LIMK1 pathway [41] and the RhoA/Rock2/Limk1 pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SMAD 7 acts as a negative regulator of the canonical TGF-β signaling pathway. Previously, it was reported that TGF-β impairs therapeutic responses to corticosteroids in chronic airway diseases and the non-canonical signaling pathway is important in this process ( 16 , 17 ). However, these reports were based on experiments using lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%